2023
DOI: 10.1186/s13395-023-00314-2
|View full text |Cite
|
Sign up to set email alerts
|

An updated C. elegans nuclear body muscle transcriptome for studies in muscle formation and function

Abstract: The body muscle is an important tissue used in organisms for proper viability and locomotion. Although this tissue is generally well studied and characterized, and many pathways have been elucidated throughout the years, we still lack a comprehensive understanding of its transcriptome and how it controls muscle development and function. Here, we have updated a nuclear FACS sorting-based methodology to isolate and sequence a high-quality muscle transcriptome from Caenorhabditis elegans mixed-stage animals. We h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
(80 reference statements)
0
2
0
Order By: Relevance
“…Throughout the years, our lab has refined the 3’UTR collection in C. elegans in the whole animal and in several somatic tissues in various stages of development 10,13,14,24,26,27 ( Main Figure 1B ).…”
Section: Introductionmentioning
confidence: 99%
“…Throughout the years, our lab has refined the 3’UTR collection in C. elegans in the whole animal and in several somatic tissues in various stages of development 10,13,14,24,26,27 ( Main Figure 1B ).…”
Section: Introductionmentioning
confidence: 99%
“…These studies, primarily conducted at the organismal or tissue levels, have revealed that miRNA expression is spatiotemporally specific, providing guidance for dissecting miRNA function during development. For instance, studies have employed methods like tissue-specific isolation or labeling of miRNAs followed by sequencing to characterize miRNAs enriched in specific tissues of interest in model organisms 13 , 17 , 20 , 22 24 . Although recent advances in single-cell genomics enable sequencing of protein-coding genes in developing cells at a single-cell resolution 25 , a similar analysis for miRNAs faces technical challenges in high-throughput sequencing of miRNAs in single cells and accurately determining cell identities.…”
Section: Introductionmentioning
confidence: 99%
“…Throughout the years, our lab has refined the 3′UTR collection in C. elegans in the whole animal and in several somatic tissues in various stages of development ( 10 , 13 , 14 , 24 , 26 , 27 ) (main Figure 1B ). Our previous C. elegans 3′UTRome (v2), which is currently available in WormBase, contains 3′UTR boundaries for 14788 genes corresponding to 23084 3′UTR isoforms (73% of all protein-coding genes included in the WS250 release) (main Figure 1B ).…”
Section: Introductionmentioning
confidence: 99%